Asymmetric Dy4 metallogrid and double-layered Dy8 cage clusters from carboxylic decorated o-vanillin Schiff bases: syntheses, topological variation, and single molecule magnet behaviors. (4th January 2023) - Wang, Yi-Han; Qin, Yu; Tang, Shen; Teng, Qing-Hu; Zhu, Meng-Meng; Peng, Song; Wang, Kai; Liang, Fu-Pei
Abstract : Two carboxylic decorated o -vanillin Schiff base ligands, which only differ in the positions of Cl-substituents, have realized the construction of an asymmetric Dy4 metallogrid and a double-layered Dy8 cage SMMs, respectively. Abstract : There is still great potential to be tapped for polynuclear lanthanide single-molecule magnets (Ln-SMMs) for performance. Toward this goal, the exploration of polynuclear lanthanide clusters (PLnCs) with novel special topologies is critical. Herein, two novel PLnCs, [Dy4 (ov6ca)6 (CH3 OH) (H2 O)2 ]·6CH3 OH·CH3 CN·H2 O (1 ) and [Dy8 (ov5ca)6 (a5ca)4 (ov)2 (μ-OH)6 ]·6CH3 OH (2 ), have been synthesized, where ov6ca 2−, ov5ca 2−, a5ca −, ov − represent the ions of 2-[( o -vanillidene)amino]-6-chlorobenzoic acid, 2-[( o -vanillidene)amino]-5-chlorobenzoic acid, 2-amino-5-chlorobenzoic acid and o -vanillin, respectively. Carboxylic decorated o -vanillin Schiff base ligands H2 ov6ca and H2 ov5ca, were constructed as 1 and 2, respectively, and only differ in the position of a Cl-substituent. However, this tiny difference has induced great variation in the nuclearity and topology between 1 and 2 . Cluster 1 features a Dy4 metallogrid core, where four Dy III ions are bridged by two Ophenol and two carboxylate groups from ov6ca 2− ligands but show different coordination geometries. To our knowledge, it is the first Ln4 cluster with such an asymmetric metallogrid topology. While 2 displays a rare double-layered cage cluster topology, in which a pair of butterfly-shaped Dy4 units were linked together by four carboxylate groups from ov5ca 2− ligands. Magnetic measurements revealed that both 1 and 2 exhibit slow magnetic relaxation behavior, with efficient energy barrier ( U eff ) values of 93.06 and 66.92 K, respectively.